Functional foods and nutraceuticals in a market of Bolivian immigrants in Buenos Aires (Argentina) - Pochettino, María Lelia (2011)
This paper presents the results of a research in urban ethnobotany, conducted in a market of Bolivian immigrants in the neighborhood of Liniers, Ciudad Autnoma de Buenos Aires (Argentina). Functional foods and nutraceuticals belonging to 50 species of 18 families, its products, and uses were recorded. Some products are exclusive from the Bolivian community; others are frequent within the community, but they are also available in the general commercial circuit; they are introduced into it, generally, through shops called dietéticas (health-food stores), where products associated with the maintenance of health are sold. On this basis, the traditional and nontraditional components of the urban botanical knowledge were evaluated as well as its dynamics in relation to the diffusion of the products. Both the framework and methodological design are innovative for the studies of the urban botanical knowledge and the traditional markets in metropolitan areas.